Attack efficacy in volleyball: Elite male teams - Castro, J.; Souza, A.; Mesquita, I. (Perceptual and Motor Skills, 2011)
The goal was to identify performance indicators predicting attack efficacy in volleyball`s game phase denominated Complex II, i.e., the counter-attack. 28 games from the 2007 Men`s World Cup were analyzed. Attack efficacy was predicted by three primary variables: Attack tempo, Attack type, and Number of blockers. Power attack and Attack tempo 1 increased the probability of an Attack point. The supremacy of Attack tempo 3 and the high frequency of Two blockers and Three blockers reflected the difficulty of efficient attack during Complex II. Despite unfavourable conditions, attackers managed to execute Power attacks in the majority of the situations, and score a high frequency of Attack points.